Pengaruh Cara Pembuatan Briket Bioarang Kopi Terhadap Kualitas Briket yang Dihasilkan - Nurohmah Jati Safitri; Tuntas Bagyono; Kamat kartono (Poltekkes Kemenkes Yogyakarta, 2020)
In the relation with the dwindling of petroleum production, other fuel alternatives are researched. The utilization of organic wastes processed as biocharcoal briquette is one of the potential alternatives which has other advantages in reducing the corresponding health and environmental unneeded effect. One of the organic wastes that potentially to be changed as biocharcoal briquette iscoffee husk. This study tried to reveal whether two types of briquette production, i.e. briquette-charcoal and charcoal-briaquette have different quality compared with the common wooden charcoal by doing an experiment which employed post-test-only-with-control-group-design. By using SPPS version 15 for windows, the statistical t-test showed that the two coffee husk briquette types were not significantly different in the time needed for water boiling and the smouldering time, however compared with the common wooden charcoal, bothtypes were proved better. In terms of the carbon content, the charcoal-briquette type has the highest percentage and has fullfiled the requisite for good briquette standard.